1997
DOI: 10.1002/(sici)1097-0215(19970106)70:1<26::aid-ijc4>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for childhood melanoma in Queensland, Australia

Abstract: The causes of cutaneous melanoma among children under 15 years are largely unknown. We report the findings of an epidemiological study of childhood melanoma in Queensland, Australia, which has the highest incidence rates in the world. All 61 cases of melanoma in children less than 15 years notified to the Queensland Cancer Registry 1987-1994 were eligible to participate in a population-based, case-control study. Data were collected through structured, face-to-face interviews with parents and skin examinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 3 publications
5
43
0
Order By: Relevance
“…Sun exposure during summer holidays or leisure-time activities were not related to melanoma risk. While this is the first study to investigate the association of sun exposure with risk of melanoma in early adulthood, there have been two previous Australian studies that examined risk factors for melanoma diagnosed in children under 15 years [18] and adolescents (15-19 years) [29]. They found that factors indicating genetic susceptibility to melanoma, such as phenotype and family history, but not measures of intermittent or continuous solar UV radiation, were associated with risk.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sun exposure during summer holidays or leisure-time activities were not related to melanoma risk. While this is the first study to investigate the association of sun exposure with risk of melanoma in early adulthood, there have been two previous Australian studies that examined risk factors for melanoma diagnosed in children under 15 years [18] and adolescents (15-19 years) [29]. They found that factors indicating genetic susceptibility to melanoma, such as phenotype and family history, but not measures of intermittent or continuous solar UV radiation, were associated with risk.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, melanomas are hypothesised to arise through divergent causal pathways, with risk differing by anatomical site of the melanoma, and the pattern and age-period of sun exposure [16,17]. Finally, the association of melanoma with UV exposure might also vary with age at diagnosis and genetic susceptibility [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Variable host and environmental factors have been identified to be associated with an increased risk of melanoma both in children and adults, including white race, fair complexion, red or blond hair, light eye color, tendency to burn with ultraviolet radiation, dysplastic nevi, congenital nevi, increased number of benign nevi, family history of melanoma, disorders of DNA repair such as xeroderma pigmentosum, immunosuppression, and a previous history of malignancy [7][8][9]. In his review of melanoma in children and adolescents, Pappo [7] divided prepubertal melanoma into 3 categories based on the age of initial diagnosis: congenital melanoma occurring from in utero until birth, infantile melanoma from birth until 1 year of age, and childhood melanoma from age 1 year until the onset of puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Q-MEGA consists of four study samples: the Queensland Study of Childhood Melanoma (N = 101), the study of Melanoma in Adolescents (N = 298), the Study of Men over 50 (N = 178) and the Queensland Familial Melanoma Project (QFMP; N = 1897) [12]. The Childhood study included children diagnosed with CMM under the age of 15 between 1987 and 1994 while the adolescent study consisted of cases diagnosed between the age of 15 and 19 in the same period [13][14][15]. In the study of men over 50, individuals were diagnosed with CMM between July 1993 and June 1994 and were at least 50 years old at diagnosis [16].…”
Section: Samplesmentioning
confidence: 99%